2011
DOI: 10.3349/ymj.2011.52.6.977
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Music Therapy on Mood in Stroke Patients

Abstract: PurposeTo investigate the effects of music therapy on depressive mood and anxiety in post-stroke patients and evaluate satisfaction levels of patients and caregivers.Materials and MethodsEighteen post-stroke patients, within six months of onset and mini mental status examination score of over 20, participated in this study. Patients were divided into music and control groups. The experimental group participated in the music therapy program for four weeks. Psychological status was evaluated with the Beck Anxiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 25 publications
2
50
0
9
Order By: Relevance
“…It was experienced while listening to music and singing [92] but also following choir participation, which may be generated by hormonal and related immune changes [18,48]. This is consistent with literature on music therapy for stroke [35,37], along with a similar study involving choral singing solely for people with aphasia [34]. However, only one study to date has indicated that music therapy showed improved mood in PD [93].…”
Section: Therapeutic Benefits Of Cstsupporting
confidence: 76%
See 1 more Smart Citation
“…It was experienced while listening to music and singing [92] but also following choir participation, which may be generated by hormonal and related immune changes [18,48]. This is consistent with literature on music therapy for stroke [35,37], along with a similar study involving choral singing solely for people with aphasia [34]. However, only one study to date has indicated that music therapy showed improved mood in PD [93].…”
Section: Therapeutic Benefits Of Cstsupporting
confidence: 76%
“…Singing employs greater neural circuitry [30,31], which may be preserved following a stroke [32]; indeed people with aphasia can often sing despite an inability to speak [33]. Small-scale singing studies with stroke survivors show improved mood [34,35], QOL [36], neuroplasticity [37], and word production [36,38]. Choral singing may also prevent voice decline [39] and improve QOL in PD [18].…”
Section: Choral Singing Therapy As a New Approach To Enhance Living Wmentioning
confidence: 99%
“…Improved mood, better relaxation, increased motor activity in music listening group (P < 0.0001) Kim et al [76] CCT (0) [78] CCT (0) Reduction of depression (P = 0.002) and fatigue (P = 0.02) and improvement in the synchronization tapping (P < 0.05) 1 Subjects expressing a clear preference for treatment (25% of total) were allocated to music therapy while all others were randomly assigned to either treatment or control group; 2 The goal of random assignment was not fully achieved because of the need to have 2-3 subject available at the same time to held group session in the treatment condition; 3 Subjects heard 1 min of music or noise and after were given all assessments while they were continuously exposed to the sound up to the end of the evaluation; 4 Patients were quasi-randomly assigned to groups making sure that the two groups were as close as possible in terms of numerosity and clinical characteristics of participants. …”
Section: Analysis Of Patient's Interviewsmentioning
confidence: 89%
“…Nine studies assessed the effects of music or MT on post-stroke patients [71][72][73][74][75][76][77][78][79] . Four of them were based on a relational approach [71,72,76,77] , three regarded music listening interventions [74,75,78] , and two used a rehabilitative approach [73,79] .…”
Section: Effects On Strokementioning
confidence: 99%
See 1 more Smart Citation